Assessment of bacterial demineralization around composite restorations using swept-source optical coherence tomography (SS-OCT). Issue 9 (September 2016) - Zhou, Yuan; Shimada, Yasushi; Matin, Khairul; Sadr, Alireza; Sumi, Yasunori; Tagami, Junji
Highlights: S. mutans biofilm created gaps at the resin–tooth interface in this in vitro model. SS-OCT could nondestructively detect composite–tooth interfacial gaps formation. SS-OCT could nondestructively detect demineralization around restorations. SE showed less resin–enamel interfacial gap depth and length than TS. SE showed significantly larger dentin lesion around restorations than TS. Abstract: Objective: To observe the bacterial demineralization of the enamel and dentin around composite restorations bonded with one-step and two-step self-etch adhesive systems using swept-source optical coherence tomography (SS-OCT). Methods: Forty class V cavities (2.5-mm surface diameter, 2.0-mm maximum depth) were prepared on cervical areas of 20 human molars. The specimens were either treated with one-step adhesive (Clearfil Tri-S Bond ND Quick; TS) or two-step adhesive (Clearfil SE Bond; SE), restored with a flowable resin composite (Estelite Flow Quick). Specimens in the demineralized group were incubated for 2 weeks after Streptococcus mutans biofilm formation, while specimens in the control group were incubated for 2 weeks without biofilms. After SS-OCT observation, specimens were cut and examined under confocal laser scanning microscope (CLSM). The lesion depth (LD), interfacial gap depth (GD) and gap length (GL) obtained from SS-OCT and CLSM were analyzed by Pearson's correlation, LD by Independent-samples t -test, GD and GL by Welch t -test, the frequency of specimens with or without gap by Fisher's exact test at the 95% significant level. Results: Specimens with interfacial gaps in the demineralized group showed significantly higher frequency than that in the control group ( p < 0.05). There was a significant correlation between SS-OCT and CLSM values of LD, GD and GL ( p < 0.05). SE showed significantly larger LD of dentin, but less GD and GL of enamel than TS ( p < 0.05). Significance: SS-OCT nondestructively detected demineralization around composite restorations and interfacial gaps created by S. mutans biofilm in this in vitro model.